Creep of Floating Ice Sheets, Computer Calculations. - Garbaccio, D. H. (1968)
Using a digital computer calculations were made of the deformations and bending moments in a floating ice sheet. The ice behavior was described by a linear viscoelastic model consisting of a Maxwell and a Voigt element in series. Loading with circular symmetry uniformly distributed was applied to a plate of finite thickness described by Reissner theory. The effect of superposed loads describing aircraft landing gear was considered. Calculations were also made for a linearized approximation to the problem of a thin sheet described by a power creep law. The method was only partially successful because the time span of applicability was short. (Author)